2018
DOI: 10.1155/2018/1825046
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Structured Physical Activity Program on Social Interaction and Communication for Children with Autism

Abstract: The purpose of this study was to investigate the effects of structured physical activity program on social interaction and communication of children with autism spectrum disorder (ASD). Fifty children with ASD from a special school were randomly divided into experimental and control groups. 25 children with ASD were placed in the experimental group, and the other 25 children as the control group participated in regular physical activity. A total of forty-one participants completed the study. A 12-week structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
19

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 21 publications
5
74
0
19
Order By: Relevance
“…Thus, the synthesis of the data showed that most researchers are studying the impact of programs using one type of PA. Only a few of them were devoted to reviewing the effectiveness of interventional programs with complex use of means. For example, relaxation exercises with the means of dance and music therapy [56], a program of mixed exercises (for example, cycling, with medicine ball) [57], programs with different ball games [58], a program with inclusion of basic coordination and strength exercises [59], a program of structured physical activity with naturally integrated elements of social interaction [60] can be attributed to comprehensive programs. In a number of studies, the efficiency of two different applications, such as muscular strength and cardiorespiratory program [53], yoga and Chinese gymnastics [61], single or triple burden running [62], dance and exercise bike exergaming [49] were compared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the synthesis of the data showed that most researchers are studying the impact of programs using one type of PA. Only a few of them were devoted to reviewing the effectiveness of interventional programs with complex use of means. For example, relaxation exercises with the means of dance and music therapy [56], a program of mixed exercises (for example, cycling, with medicine ball) [57], programs with different ball games [58], a program with inclusion of basic coordination and strength exercises [59], a program of structured physical activity with naturally integrated elements of social interaction [60] can be attributed to comprehensive programs. In a number of studies, the efficiency of two different applications, such as muscular strength and cardiorespiratory program [53], yoga and Chinese gymnastics [61], single or triple burden running [62], dance and exercise bike exergaming [49] were compared.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown a positive effect of PA on academic activity and academic performance [39,81,82] of people with ASD, as well as improving their cognitive function [60,68]. It was found that every 10th research is devoted to the issues of cognitive skills under the influence of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, physical activity is important for everyone not only for having good physical health but also for good psychological health which is necessary for a better life and doing better things. Sports provide interaction and communication and develop cooperation between individuals (Zhao & Chen, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Esse estudo mostra taxas de melhoria por aspetos avaliados, sendo eles: atenção (22%), percepção 32%, tônus 46%, o ajuste do motor 86%, imitação 60%, emoção 16%, contato 37%, e de comunicação 24% (HAMEURY, 2010). Uma pesquisa bem mais recente nos mostra resultados positivos na relação exercício físico x melhoria na comunicação em crianças com autismo, utilizando o método experimental com uma amostra de 41 crianças (ZHAO;CHEN, 2018).…”
Section: Comportamento Socialunclassified